Freshness ratio of information: a new metric for age of information. Issue 3 (1st February 2020) - Lee, Y.
Abstract : The age of information is the time elapsed since the generation of the last successfully received update message. In this Letter, the authors propose a new metric, freshness ratio of information (FRoI), defined as the fraction of time the age does not exceed a predefined freshness threshold. In addition, they analyse the FRoI for two different system models.